Business continuity planning / Patricia Alisha Petrus - Petrus, Patricia Alisha (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
An all-encompassing endeavour to prioritise critical business activities and detect serious threats to regular operation. It also includes measures for mitigation (improvement) to enable an effective and efficient organisational response to issues that arise during and after a crisis. As a result, this strategy will ensure that all corporate records are safeguarded.